2020
DOI: 10.1111/aphw.12231
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Health Action Process Approach to Social Distancing Behavior During COVID‐19

Abstract: Background This study examined the social cognition determinants of social distancing behavior during the COVID‐19 pandemic in samples from Australia and the US guided by the health action process approach (HAPA). Methods Participants (Australia: N = 495, 50.1% women; US: N = 701, 48.9% women) completed HAPA social cognition constructs at an initial time‐point (T1), and one week later (T2) self‐reported their social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 64 publications
13
69
1
1
Order By: Relevance
“…In the motivation phase, action self-efficacy was a stable predictor of intention for both behaviors, which concurred with the previous studies indicating self-efficacy played a prominent role in health-related behavior, such as social distancing and hand hygiene during COVID-19 (Derksen et al, 2020 ; Hamilton et al, 2020 ). Outcome expectancies didn’t predict intentions as expected.…”
Section: Discussionsupporting
confidence: 89%
“…In the motivation phase, action self-efficacy was a stable predictor of intention for both behaviors, which concurred with the previous studies indicating self-efficacy played a prominent role in health-related behavior, such as social distancing and hand hygiene during COVID-19 (Derksen et al, 2020 ; Hamilton et al, 2020 ). Outcome expectancies didn’t predict intentions as expected.…”
Section: Discussionsupporting
confidence: 89%
“…More frequent guideline adherence also was indirectly associated with greater openness to experience via positive attitudes toward guidelines. Related research has shown intentions to be associated with social distancing behavior and other preventive behaviors, including hand washing, respiratory hygiene, and staying at home [ 4 , 5 , 8 ]. Evidence suggests more frequent mask-wearing is positively associated with beliefs about related behavioral outcomes, need for cognition, self-control, risk aversion, and more liberal political orientation and negatively associated with beliefs in misinformation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, three studies reported that intention and confidence to perform/maintain a COVID prevention behaviour (self-efficacy) were consistently associated with self-reported behaviour one week later (12-14). Two of these studies also measured action planning and self-monitoring and observed that these constructs predicted distancing behaviour(12, 13). In contrast, there is mixed evidence that risk perception, social and moral norms, and belief in the behaviour’s utility contribute to distancing behaviour, although these are often reported as correlates of COVID prevention behaviours in cross-sectional studies (15-21).…”
Section: Introductionmentioning
confidence: 99%